Development and psychometric evaluation of an occupational health and safety performance tool for manufacturing companies - Abolfazl Ghahramani; Mahboub Ebrahimi; Mohammad Hajaghazadeh (Heliyon, 2023)
Background: The occupational health and safety (OHS) performance of organizations maybe affected by internal and external factors. According to a literature review, standardized tools for studying these factors are limited. Therefore, the main aim of this study was to examine psychometric properties of a tool for evaluating OHS performance. The tool was used to investigate the relationship between the identified OHS performance influencing factors and occupational injury. Methods: The questionnaire developed through conducting a literature review about the OHS performance and constructing a question pool. The number of items was reduced to 93 after performing a screening process. Sixteen OHS scholars offered feedback on the tool's phrasing and applicability to check face and content validity. Test-retest reliability was examined through intraclass correlation coefficients. 850 questionnaires were distributed at 12 manufacturing companies in the West Azerbaijan province in Iran, 600 valid questionnaires were returned. Exploratory and confirmatory factor analysis were conducted to assess construct validity. Criterion validity was investigated by measuring agreement between its OHS performance scores and occupational injury. A set of regression analyses examined the variables associated with OHS influencing factors. Results: Validity analysis revealed that 93 items had an excellent content validity ratio (>0.79) and content validity index (>0.47). The exploratory factor analysis resulted in eleven OHS performance factors. Thirty-three items were removed because of inadequate reliability. The result of confirmatory factor analysis showed that the OHS performance model is satisfactory. The final 60-item scale's reliability score was 0.96. The safety system was identified as the main influencing factor (3.54 ± 0.65). Participants with more safety training reported more injuries. Safety training and injury experiences, company size, and occupational health and safety management system (OHSMS) adoption affected OHS performance influencing factors. Occupational injuries were linked to company size (OR = 1.39, CI = 1.06–1.82), whereas the absence of OHSMS was connected with an increased risk of occupational injury (OR = 0.09, CI = 0.02–0.55). Conclusions: The developed tool had satisfactory psychometric properties for assessing OHS performance in manufacturing companies. OHS performance could be improved by implementing safety systems and focusing more on incentive programs. Implementing the requirements of an OHSMS may improve the OHS performance and decrease occupational injuries.